Ultrasonography of ovine pulmonary adenocarcinoma. Issue 7 (31st August 2018) - Scott, Phil; Cousens, Chris
Abstract : Ovine pulmonary adenocarcinoma (OPA) is a contagious and fatal lung tumour caused by Jaagsiekte sheep retrovirus. This article presents images from ultrasound and postmortem examination of OPA lesions, and other common lung pathologies in adult sheep. Video recordings are also provided with the online version of this article. We would encourage veterinary practitioners to use the images and videos provided in this article as a reference repository when they are investigating OPA lesions on farm.